(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In this paper I have examined the Companies (Amendment) Bill, 2016 in which overview of the significant perspectives and changes incorporated in the bill in light of the CLC report and also discussed the Standing Committee report. It likewise endeavors to analyze whether the progressions incorporated in the bill are to the greatest advantage of the companies and whether these progressions will truly help in accomplishing the objectives envisaged by the Ministry of Corporate Affairs.